Integrating Social Support into the TAM Framework: Effects on ‎E-Learning Usage and Acceptance - Wighneswara, Alifiannisa Alyahasna; Yuhana, Umi Laili (Newinera Publisher, 2024)
This research explores the role of social support in the context of the TAM model in relation to usage and acceptance of e-learning by high school learners as well as a technical usability assessment of e-learning environment. By employing cross sectional survey design and Partial Least Squares Structural Equation Modeling (PLS-SEM analytical technique, we explore the interconnection of social support with perceived usefulness, perceived ease of use, behavioral intention and actual usage. Specifically, the work finds that social support partially mediates students’ reception of e-learning from their perspective of perceived usefulness and its ease of use and that perceived usefulness is deeply seated in behavioral intention on the chosen platform. From the technical analysis, load testing, content delivery and security was examined to determine the effectiveness of the platform. An addition of a content delivery network streamlined page load time and minimized latency issues while on security the implementation of SSL and two factor authentication advanced the security of data. These are tangible technical enhancements accompanied by social support systems which increase the e-learning derived adoption as well as the retention ratios. The implications of the results put emphasis on both social and technical aspects in e-learning system that must be taken into consideration for educators and developers creating efficient and large-scale e-learning system.